Peran Generasi Z dalam Mendorong Viralitas Musik Lokal via TikTok: Systematic Literature Review - Arshita Lutfi Alfionita; Rosalinda; Nabila Rahmadani; Olga Karin Bell; Alivia Arliana; Nandha Narendra Muvano (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
This study aims to examine the role of Generation Z in driving the virality of local music through the social media platform TikTok. The development of digital technology and social media has changed the patterns of music production, distribution, and consumption, with TikTok becoming one of the main platforms in shaping music trends, especially among the younger generation.Generation Z, as digital natives, possess creative, adaptive, and participatory characteristics that make them key actors in creating and spreading viral music content. This study employs a Systematic Literature Review (SLR) method with a qualitative approach to various national and international journals relevant to the topics of Generation Z, TikTok, and the virality of local music.The results of the study indicate that the virality of local music on TikTok is not only influenced by the platform's algorithm but is also significantly determined by creativity, active participation, digital literacy, and Generation Z's ability to read and shape digital trends. Creative strategies such as challenges,dance trends, the use of background music, remixes, and digital social interaction are key factors in increasing the exposure and popularity of local music.However, this study also found that limitations in data analysis capabilities and utilization of TikTok's strategic features remain obstacles to the effectiveness of local music promotion. Therefore, developing Generation Z human resources through digital training and ongoing mentoring is a crucial factor in optimizing the virality of local music in the era of the digital creative economy.